On common fixed point via inverse Ck-class functions in partially E-cone metric spaces - Meitei, M. Solomon; Singh, L. Shambhu; Singh, T. Chhatrajit (Fixed point theory and algorithms for sciences and engineering, 2025)
In this paper, we introduce common fixed point theorems through the context of inverse C k -class functions on partially E -cone metric spaces. We extend the existing fixed point theorem and explore the existence and uniqueness of common fixed point theorem under some compatible conditions such as semi-compatibility, semi-compatibility of type (A), weak semi-compatibility, conditional semi-compatibility and Sτ –compatibility. Examples are given to bolster our findings.